Responsabilidad Penal Atenuada de los Sujetos Activos por Trastorno Mental Transitorio en el Cometimiento De Delitos - Muñoz Flores, Jandry Santiago (2018)
The investigation work entitled: "Attenuated criminal liability of active subjects for transient mental disorder in the commission of crimes", refers to a problem of social legal reality; the person who transgresses the regulation with his diminished cognitive and volitional faculties, is not capable of understanding the illicit produced or of knowing the scope of his acts. Transient mental disorder is a state of experiential reaction to exogenous factors that are so strong that they produce a transient alteration in the minds of people. The Constitution of the Republic of Ecuador guarantees legal security and the application of a proportional sanction according to the damage caused and the mental state of the person processed. Article 36 of the Comprehensive Criminal Organic Code does not guarantee the proportional principle of punishment and legal certainty, since not maintaining the difference between a mental illness and a simple experiential reaction that clouds the capacities of the active subject of the crime, creates confusion in community; and, it makes it difficult for judges to correctly apply sanctions to unlawful acts. The specification of the transitory mental disorder within Comprehensive Criminal Organic Code will allow the person being prosecuted to be judged correctly, thus guaranteeing that the legal security and the proportional principle of punishment is not violated. The person with this type of transient anomaly will be attentively responsible since their behavior is the effect of a simple reaction to the stimuli of the family, cultural, social and academic environment.